Deradicalization in The Novel Demi Allah Aku Jadi Teroris by Demien Dematra - Ahmad Sunardi; Teguh Supriyanto; Fathur Rokhman; Agus Nuryatin (Universitas Negeri Semarang, 2022)
A literary work will be valuable if it has benefits in real life. One of the unfinished problems in the life of the nation and state today is terrorism which needs to be handled seriously and comprehensively. One of the preventive steps to prevent terrorism can be carried out through deradicalization messages in a literary work. The purpose of this paper is to describe the forms of deradicalization in Demian Demattra novel Demi Allah, Aku Jadi Teroris. The methodology used is dialectical with a sociological approach to literary works. The results of this study are forms of deradicalization in accordance with Government Regulation of the Republic of Indonesia Number 77 of 2019 Article 31, namely 1) the form of identification carried out by the police when identifying suspected terrorists, 2) the form of law enforcement, namely the hunting and arrest of suspected terrorists carried out by the police, 3) the form of reeducation, namely the essential religious education of Kemala, and 4) the form of social integration carried out by Kemala after being released from prison. Messages to readers and future researchers should continue to broadcast the deradicalization program through literary works that can be applied to the community.